Flexicurity strategies on the economic crisis background - PAŞNICU, Daniela; MLADEN, Luise (Annals of Spiru Haret University. Economic Series, 2010)
The flexicurity concept – a combination of flexibility and security strategies, specific to each country – is a successful outcome[1] of the 2010 Lisbon Strategy. Ever since 2000, this concept has been implemented for continuing the European labour markets reform. The conclusion of the Mission for Flexicurity[2] is that the European labour markets challenges have not changed, therefore flexicurity is the strategy to be further implemented in order to align to the new competition requirements, providing also the necessary social protection, especially on the current economic crisis background. The paper addresses the flexicurity concept development, the implications of the flexicurity strategies and of the steps taken on the European Union Member States labour markets, on the economic crisis background.